EVALUASI PENGGUNAAN ANTIBIOTIK PADA PASIEN PNEUMONIA DI RUMAH SAKIT UNIVERSITAS SEBELAS MARET DENGAN METODE GYSSENS - Sawitri, Satwika Budi; Hidayah, Firda Himayatul; Azzahro, Azzar; Fatihah, Nadia Iha (PC IAI Sragen, 2025)
Pneumonia is an infectious lung disease that is a worldwide problem and causes high mortality and morbidity rates. Pneumonia is an acute infectious disease that hits the lung tissue (alveoli), a cold cough disease accompanied by shortness of breath or rapid breathing. The disease can be found in toddlers, adults, and old age. This study aims to determine the pattern of antibiotic prescribing and evaluation of antibiotic use in pneumonia patients in the inpatient installation of Universitas Sebelas Maret Hospital for the 2021 period. Qualitative descriptive research method by retrospectively taking medical record data of Pneumonia patients at Universitas Sebelas Maret Hospital. The results showed a pattern of pneumonia patients based on male as many as 17 (53%) patients and female patients as many as 15 (47%). Patients were hospitalized for less than 7 days as much as 91% and most were given injection routes as much as (91%). The pattern of antibiotic use was 54 antibiotics, with the highest percentage of ceftriaxone antibiotics as much as 35%. The results of the qualitative evaluation of antibiotic use with a sample of 32 medical records showed that antibiotic prescribing was by the guidelines with the details of category 0 as many as 43 prescriptions (80%), category IIB as many as 1 (2%), category III B as many as 5 prescriptions (9%), and category IVC as many as 5 (9%).